A systematic review of decellularized allograft and xenograft–derived scaffolds in bone tissue regeneration. (April 2021) - Amini, Zahra; Lari, Roya
Highlights: Decellularized tissues can be considered as a safe and promising alternative for a bone graft. The applications of decellularized allograft and xenograft tissues in bone regeneration have been systematically reviewed. Decellularization protocols, various types of cells used for recellularization, and in vivo implantation have been investigated. Based on this study, the decellularized xenograft-derived bone scaffolds can be considered as an alternative to the autologous bone graft. Abstract: Bone substitutes are used in nearly half of all musculoskeletal surgeries. The "gold standard" graft is an autograft that is limited by supply and site morbidity. Therefore, allograft sources are the current alternative for clinical practice with some side effects, such as immune responses and risk of disease transmission. In this paper, we have systematically reviewed the development and characterization of decellularized allograft or xenograft-derived scaffolds as bone graft substitutes. The databases of PubMed, Cochrane, Scopus, and Web of Science were searched for experimental studies that investigated the potential of acellular allograft or xenograft-derived scaffold for bone regeneration. The search was finalized on 14 September 2020. The initial electronic database search resulted in a total of 484 studies. During the screening process, 416 studies were excluded due to not meeting the inclusion criteria. Finally, a total of 68 articles were included, in which human or animal tissues have been decellularized for bone tissue generation purposes. Although in most studies, a decellularized bone was used for the generation of a bone scaffold, other decellularized tissues, such as the human amniotic membrane or human adipose tissue, were also used in some researches for this purpose. In 42 studies out of the 68, decellularized bone scaffolds were implanted into in vivo animal models. 8 studies used animal bone tissues as an allograft. 12 studies used human tissues as a xenograft. The studies have shown that decellularized allograft or xenograft scaffolds have high biocompatibility with little or no host response, and can enhance new bone formation. Overall, the results of this study suggest that the decellularized xenograft-derived cancellous bone scaffolds can be considered as alternatives to the autologous bone graft. This systematic review might affect future research directions and the preoperative planning of graft selection.